CRIMINAL LAW ENFORCEMENT FOR NON-MUSLIMS IN ACEH - Nurochman Nulhakim; T Riza Zarzani N (PT. Sinergi Legal Publisher, 2025)
This study examines the legal and sociological implications of the implementation of the Qanun on Jinayat Law against non-Muslims in Aceh within the framework of the national legal system and efforts to realize substantive justice. The application of the qanun to non-Muslims is legally legitimized through Law Number 11 of 2006 concerning the Governance of Aceh, specifically Article 129, which provides a legal basis for voluntary and automatic submission. However, the mechanism of submission in practice often raises serious problems, because choices that are normatively called voluntary are in reality often merely formalities due to social pressures or pragmatic considerations. This phenomenon creates a dilemma between formal legal certainty and the protection of the basic rights of non-Muslims guaranteed by the constitution. Sociologically, non-Muslims in Aceh are more likely to submit to the Qanun Jinayat (Islamic Law) than to the Criminal Code (KUHP), as caning is seen as a lighter, quicker punishment, and carries less long-term stigma than imprisonment. However, this choice is not a form of substantive acceptance, but rather a coping strategy reflecting social pressure and potential discrimination. This raises critical questions about the extent to which regional laws can harmonize with the constitutional principles of equality before the law and non-discrimination. The research findings indicate that the application of the Qanun Jinayat to non-Muslims is legally valid, but constitutionally and sociologically problematic. To realize substantive justice in Indonesia's rule of law, a clear and transparent reformulation of the submission mechanism is required, along with strict oversight by the central government to prevent Aceh's special autonomy from giving rise to discriminatory practices. Thus, legal pluralism in Indonesia can operate in harmony with the principles of a democratic rule of law that guarantees the protection of the rights of all citizens without exception.